Dendrogramas de manejo da densidade para povoamentos de Pinus elliottii Engelm para a região central do Rio Grande do Sul - Thomas, Cláudio (2009)
This work aimed at building a management dendrogram and determining the appropriate density for management of stands of Pinus elliottii in central region of the Rio Grande do Sul. To do that, stands in maximum stock, in different ages, located in the campus of Universidade Federal de Santa Maria and neighborhoods, were used. The dendrometric variables used in the calculation process were obtained from sample units with temporary characteristic, considering the method of determination of the punctual density proposed by Spurr, and isolated trees, with crowns in free growth. The maximum population density was estimated by the Reineke method, with an angular coefficient of -1,92009. The density in number of trees for the beginning of the total occupation of the dossal was estimated taking into account the crown areas, which were obtained from a lineal model estimator of crown diameter in function of the dap, fit for variables from trees in free growth. The construction of the dendrogram was in function of the basal area, the number of trees per hectare and the tree diameter with medium basal area. The density levels were determined proportionally to the maximum density for stands density index (IDP), in clusters of index 200, from the maximum IDP, 1200, to the minimum, 400. The appropriate density for management was found by calculation process and adjusted by the observation of two stands. Results indicate the maintenance of the density between IDP 600 and 840 for the production of wood of great dimensions. Plans of management with different initial densities and number of self-thinning interventions were elaborated, showing that the dendrogram is an efficient tool, able to assist the elaboration of the management plan, with production estimates for self-thinning and final cut.